PARADOKS PELAYANAN PUBLIK: Standar Tinggi Versus Realita Lapangan dalam Persetujuan Bangunan Gedung di Kota Kendari - La Ode Muhammad Elwan; Taufik; Marni; Kasman (Halu Oleo University, 2025)
This study aims to determine the Paradox of Public Service by criticising High Standards Versus Field Reality in Building Approval in Kendari City. The data sources used are primary data and secondary data. Primary data is data created by researchers for the specific purpose of solving the problems they are handling. Secondary data is data that has been collected for purposes other than solving the problems being faced. This data can be found quickly. The informants in this study were 1 Head of Spatial Planning Section, 1 Spatial Planning Staff, and 4 PBG applicants. The research findings show that the Building Approval Service (PBG) at the PUPR Office of Kendari City has used a one-stop model according to its duties and authorities, but has not fully met public service standards. Complicated procedures, long completion times, and unclear costs hinder the effectiveness of services and open up opportunities for practices outside the provisions. For this reason, it is necessary to simplify procedures, accelerate service times, transparent costs, improve facilities, and strengthen the competence of officers so that PBG services can run more effectively, efficiently, and accountably.